Diversity and abundance of primates in low and high human disturbance forests of Los Chilchos, Amazonas, Peru - Aquino, Rolando (2018)
In the montane forests of Los Chilchos five species of primates inhabit, whose current situation, group size and abundance are unknown, which are indispensable for the management and formulation and implementation of conservation measures. In order to obtain information on the mentioned aspects, censuses were conducted by linear transect between June and July 2017 in forests of low and high anthropic disturbance. As a result of the censuses, 63 groups belonging to 5 species were registered. Of these, 50 groups corresponded to low disturbance forests, being Aotus miconax and Ateles belzebuth the most observed with 21 and 17 groups, respectively. Larger groups were observed in Cebus yuracus (average 17.0 ± 5.0 individuals) and A. belzebuth (average 14.5 ± 7.2 individuals) and smaller in A. miconax (average 2.6 ± 0.7 individuals). With exception of Lagothrix flavicauda, the relative abundance and population density were higher in low-disturbance forests, demonstrating thus the good conservation status, which does not occur in high-disturbance forests. Among primates, the highest density was for A. miconax with 26.23 indiv. /km2 and the lowest for Alouatta seniculus with 3.0 indiv./km2. Lagothrix flavicauda was recorded only in high disturbance forest, whose relative abundance was estimated at 0.1 groups / 10 km.